Influence of weight status at 2 years on memory performance at 4–5 years of age - Simone de Kácia Wendt; Bruna Constantino; Edimari A. Wendt; Marco F. Mastroeni (Annals of Human Biology, 2019)
Background: Memory performance is a cognitive function that is affected by environmental, genetic and socioeconomic factors, as well as by weight status. Aim: To evaluate the association of weight status at 2 years of age with the memory performance of children at 4–5 years of age. Subjects and methods: A cross-sectional study that used baseline data (2012) and data from two follow-up periods (2014 and 2016) of the PREDI Cohort Study. Participants were mother–child pairs 4–5 years after delivery who were seen between July 2016 and August 2017. The children’s memory performance was evaluated individually using a validated Brazilian instrument. Results: Of the 203 children included in the study, 117 (57.6%), 52 (25.6%) and 34 (16.8%) had low, moderate and high memory performance, respectively. After adjusting for potential confounders, children with a BMI > 85th percentile had 3.33-times higher odds of exhibiting lower memory performance at 4–5 years of age than those with a BMI ≤ 85th percentile. In addition to the children’s BMI at 2 years of age, mother’s education was another independent determinant of children’s memory performance. There was a progressive increase in the odds of children having lower memory performance at 4–5 years of age as the mother’s education decreased. Conclusion: Primary prevention of overweight and management of cognitive functions may be important strategies to improve the cognitive development of children in the future.